TECHNOLOGY FOR OBTAINING REDUCED IRON FROM PYRITE CINDERS - Eshonkulov U.Kh; Turdiev Zh.N (Western European Studies, 2024)
Chemically pure iron is a shiny silvery-white viscous and malleable metal with a density of 7.8 g/cm3 and a melting point of 1539±1 °C. The most common are iron-carbon alloys (cast iron, steel), iron-manganese alloys (ferromanganese), silicon (ferrosilicon), chromium (ferrochrome), tungsten, vanadium, titanium, niobium, cobalt, nickel, molybdenum, etc. playing a leading role in modern technology
Keywords: technology; vanadium; cobalt; Chemically